Nutrition and Exercise Interventions for Stem Cell Exhaustion in Aging - Hendrata, Winona May; Muliarta, I Made (LifeSciFi, 2025)
Aging is characterized by progressive stem cell exhaustion, leading to impaired tissue regeneration and organ dysfunction. While stem cell transplantation has been extensively explored for aging interventions, preserving endogenous stem cell function through lifestyle strategies might offer a more sustainable approach. This review synthesizes current evidence on how nutritional interventions and physical exercise can mitigate stem cell decline by targeting shared aging pathways. The research method in this study uses narrative review with a systematic approach through literature search in PubMed, Scopus, and Springer Link databases, using combined keywords, MeSH terms, and snowballing techniques. Nutritional interventions, including caloric restriction and fasting-mimicking diets, enhance stem cell resilience through metabolic reprogramming involving AMPK, mTOR, and autophagy restoration. Plant-derived polyphenols such as fisetin and quercetin emerge as promising adjuncts, targeting senescence clearance and optimizing the stem cell niche. Exercise concurrently activates stem cells via mechanosensitive pathways and systemic factor release while also improving polyphenol bioavailability through enhanced tissue perfusion. Senolytic safety requires careful evaluation due to senescence’s tumor-suppressive role, while polyphenol bioavailability limitations may be addressed with nanocarriers and structural modifications. By integrating lifestyle and nutraceutical strategies, this multi-dimensional approach offers a roadmap for maintaining endogenous stem cell pools and extending healthspan.